A EDUCAÇÃO DO CORPO NA FORMAÇÃO DE PROFESSORES NA ESCOLA NORMAL PAULISTA (1890-1931) - Honorato, Tony; Nery, Ana Clara Bortoleto [UNESP] (Centro de Estudos Educação e Sociedade, 2018)
In the state of São Paulo, Brazil, the Normal School was responsible to spread pedagogic innovations and diffuse new knowledge and practices for primary school. We assume that physic and aesthetic corporal practices, producers of a body education and offered in Normal School, were those reformers and public institution officials who broadcast interest in having an impact grade schools, focusing on social regeneration. So, which practices composed a sense of this education of the body in teacher’s training (1890-1931)? As a result, we focused the analyses on gymnastics and scouting.

A Escola Normal Paulista foi lócus de promoção de inovações pedagógicas e de irradiação de saberes e práticas ao magistério primário. As práticas corporais de cultivo físico e estético, produtoras de uma educação do corpo, eram aquelas que os reformadores e os agentes da instrução pública tinham o interesse de difusão para ter um impacto sobre as Escolas Primárias, foco da regeneração social. Então, quais práticas que compuseram um sentido de educação do corpo estavam presentes na formação de normalistas (1890-1931)? Como resultado, centramos análises sobre a Ginástica e o Escotismo.
The education of the body in teachers’ training in Normal School of the state of São Paulo (1890-1931)
Keywords: Education of the body; Gymnastic; Scouting; Normal School; Pedagogical printed; Educação do corpo; Ginástica; Escotismo; Escola Normal; Impresso pedagógico